REFORMA AGRARIA: MOMENTUM KEADILAN DAN KESEJAHTERAAN - Tri Chandra Aprianto (Pusat Penelitian dan Pengabdian kepada Masyarakat, Sekolah Tinggi Pertanahan Nasional, 2014)
At least there were two types of political events at the time of the implementation of agrarian reform in Indonesia,in both the process and practice. However, both events were not adequately used. As a result, the justice and welfare for poorIndonesian farmers were not yet fulfilled. The opportunity should be gained in order to implement the agrarian reform by theauthoritative actor assisted by an institution various social sheltering social forces.Key words: agrarian reform, political momentum, agrarian justice